Implikasi Program Kegiatan Keagamaan dalam Pembiasaan Solat Duha dan Baca Al-Qur'an - Luthfan Amna Sya'ban Faturrohman; A. Mujahid Rasyid; Huriah Rachmah (Bandung Conference Series: Islamic Education, 2023)
Abstract. The background of this research is where educators see students who are not accustomed to praying Duha and reading the Qur'an, therefore educators and schools from SMPN 36 Bandung want to implement a program of religious activities in the habit of praying Duha and reading the Qur'an. and for the students. The purpose of this religious activity program is to familiarize and apply it in everyday life for all students. This research uses a qualitative descriptive method to analyze the data use data collection, data reduction and data presentation. Based on the results of data processing, planning is carried out based on evaluation, namely the person in charge of this religious activity program forms an implementing team or often referred to as PPK, the formation of the SMPN 36 Character School Team is tasked with making PPK-based curriculum development documents, implementing quality assurance for the implementation of KDP Jagar is going well in the future, the implementation of this religious activity program is neatly arranged, namely online through software such as Zoom, for the final evaluation of this religious activity program all students are required to write down all religious activities that have been carried out through an assignment book and fill out the final evaluation through the google form that has been provided by the person in charge of the program.Abstrak. Kajian penelitian ini dilatar belakangi pendidik melihat kondisi peserta didik yang belum terbiasa melaksanakan sholat duha dan baca Al-Qur’an, maka dari itu pendidik dan pihak sekolah dari SMPN 36 Bandung ingin menerapkan program kegiatan keagamaan dalam pembiasaan sholat duha dan baca Al-Qur’an bagi peserta didiknya. Tujuan dari program kegiatan keagamaan ini yaitu bertujuan untuk membiasakan dan menerapkannya dalam kehidupan sehari-hari bagi semua peserta didiknya. Untuk penelitian ini menggunakan metode deskriptif kualitatif, untuk menganilisis data yaitu pengumpulan data, reduksi data dan penyajian data. Berdasarkan hasil dari pengolahan data, perencanaan yang dilakukan berdasarkan evaluasi, yaitu penanggung jawab dari program kegiatan keagamaan ini membentuk Tim pelaksana atau sering disebut dengan PPK, terbentuknya Tim Sekolah Karakter SMPN 36 ini bertugas untuk membuat dokumen pengembangan kurikulum berbasis PPK, melaksanakan penjaminan mutu pelaksanaan PPK jagar terlaksana dengan baik kedepannya , pelaksanaan dari program kegiatan keagamaan ini tersusun dengan rapi yaitu secara online melalui perangkat lunak seperti zoom, untuk evaluasi akhir dari program kegiatan keagamaan ini semua peserta ddik diwajibkan menulis semua kegiatan keagamaan yang sudah dilaksanakan melalui buku tugas dan mengisi evaluasi akhir melalui google form yang sudah disediakan oleh penanggung jawab dari program tersebut.